Comparison of Problem-Based Learning and Discovery Learning To Improve Students' Mathematical Critical Thinking Skills - Anderson Leonardo Palinussa; Johanis Stefanus Lakusa; La Moma (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2023)
The learning model applied in mathematics learning is expected to shape, develop and even improve students' critical thinking skills. This study aimed to: (1) analyze the differences in the improvement of students' mathematical critical thinking skills between students who learn to use the Problem Based Learning model and students who use the Discovery Learning model, and (2) to find out the interaction between the learning model and students' initial mathematical abilities towards improving their students' mathematical critical thinking ability. The research used a quasi-experimental type with a 2 x 3 factorial design that uses a two-way analysis of variance technique. This research took place at Public Senior High School 6 Ambon. The test instrument used was in the form of descriptive questions, which are based on indicators of mathematical critical thinking skills, according to Facione. Data analysis carried out in this research was in the form of normality test, homogeneity test, gain index analysis, and hypothesis testing. The research hypotheses were tested using Two-Way ANOVA. The results obtained indicate that: (1) there is no difference in increasing mathematical critical thinking skills between students who learn by using the Problem Based Learning learning model and students who learn by using the Discovery Learning learning model, and (2) there is a difference in the improvement of students' mathematical critical thinking skills based on their students' initial mathematical abilities, (3) learning models and students' initial mathematical abilities are believed to be 95 percent able to influence the improvement of students' mathematical critical thinking skills.